2009
DOI: 10.1097/ccm.0b013e31819598af
|View full text |Cite
|
Sign up to set email alerts
|

Alkaline phosphatase treatment improves renal function in severe sepsis or septic shock patients*

Abstract: In severe sepsis and septic shock, infusion of AP inhibits the upregulation of renal inducible NO synthase, leading to subsequent reduced NO metabolite production, and attenuated tubular enzymuria. This mechanism may account for the observed improvement in renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(83 citation statements)
references
References 26 publications
4
79
0
Order By: Relevance
“…Systemic IAP was well tolerated and had little to no observed toxicity or side effects. [60] Septic patients who received IAP had significant improvement in kidney function, as demonstrated by decreases in median plasma creatinine levels and creatinine clearance. [61, 62] This was associated with the IAP treated patients having a trend towards reduction in dialysis requirement and duration.…”
Section: Specific Surgical Disease Where Iap May Play a Role In Diseamentioning
confidence: 99%
“…Systemic IAP was well tolerated and had little to no observed toxicity or side effects. [60] Septic patients who received IAP had significant improvement in kidney function, as demonstrated by decreases in median plasma creatinine levels and creatinine clearance. [61, 62] This was associated with the IAP treated patients having a trend towards reduction in dialysis requirement and duration.…”
Section: Specific Surgical Disease Where Iap May Play a Role In Diseamentioning
confidence: 99%
“…Alkaline phosphatase (AP) is an endogenous enzyme that exerts detoxifying effects through dephosphorylation of endotoxins and pro-inflammatory extracellular ATP and is reduced during systemic inflammation. Heemskerk and colleagues [64] demonstrated that AP application was associated with a decreased expression of iNOS synthase in proximal tubule cells isolated from urine related to an attenuated urinary excretion of an proximal tubule injury marker. In a small, randomized trial, Pickkers et al showed that the administration of exogenous AP in septic patients improved endogenous creatinine clearance and reduced the requirement and duration of renal replacement therapy [65].…”
Section: Potential For Diagnostic and Therapeutic Targetsmentioning
confidence: 99%
“…Clinical trials showed renal protective effects of bovine intestinal alkaline phosphatase in critically ill patients with sepsis-associated acute kidney injury (AKI) [1,2]. Recently, human recombinant AP (recAP) was developed as a pharmacological attractive replacement.…”
Section: Introductionmentioning
confidence: 99%